2010
DOI: 10.1111/j.1365-294x.2010.04954.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the single lineage of transmissible ‘social cancer’ in an asexual ant

Abstract: How cooperation can arise and persist, given the threat of cheating phenotypes, is a central problem in evolutionary biology, but the actual significance of cheating in natural populations is still poorly understood. Theories of social evolution predict that cheater lineages are evolutionarily short-lived. However, an exception comes from obligate socially parasitic species, some of which thought to have arisen as cheaters within cooperator colonies and then diverged through sympatric speciation. This process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…Studies of experimental evolution using microbial cooperative systems have demonstrated the importance of high relatedness in their evolution (22,49). In P. punctatus, our previous population genetics study showed that the rate of worker migration among colonies in the study population was very low, at ∼10 −5 per generation (40). The restriction of migration is likely explained by the operation of a nestmate discrimination system [although condition-dependent to some extent (51-54)].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Studies of experimental evolution using microbial cooperative systems have demonstrated the importance of high relatedness in their evolution (22,49). In P. punctatus, our previous population genetics study showed that the rate of worker migration among colonies in the study population was very low, at ∼10 −5 per generation (40). The restriction of migration is likely explained by the operation of a nestmate discrimination system [although condition-dependent to some extent (51-54)].…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study indicated that cheaters had a much higher migration rate among colonies than cooperators, estimated at 10 −2 per generation (40). Therefore, cheaters can avert the immediate extinction of their own lineage by acting like a "transmissible social cancer" (40,58). The differential migration rates might be explained by the adaptation of the cheaters during the time they adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thelytoky has already led to the evolution of specialised social parasites as in the Cape honeybee A. m. capensis (Goudie and Oldroyd, 2014) and the ant Pristomyrmex punctatus (Dobata et al, 2009;Dobata et al, 2011). In the Cape honeybee the consequences of the parasitic lineage are devastating.…”
Section: Discussionmentioning
confidence: 99%